Inverse relationship between coarse food grain intake and blood pressure among young Chinese adults - Liu, X; Liao, X; Gan, W; Ding, X; Gao, B; Wang, H; Zhao, X; Liu, Y; Feng, L; Abdulkadil, W; Li, Y (Oxford University Press, 2018)
Background Coarse food grains are rich in dietary fiber and contain a wide range of nutrients with potential health benefits, such as blood pressure control. Coarse food grains are very popular in China, where hypertension is a major challenge. We evaluated the associations between coarse food grain consumption and blood pressure among young Chinese adults. Methods A total of 104 men and women aged 18–35 years, who participated in a pilot study of the Carbohydrate Alternatives and Metabolic Phenotypes study, were included in the present analysis. Food frequency questionnaires were used to collect dietary intake data. Blood pressure was measured using a digital monitor. A multivariate general linear model was used to evaluate the putative associations. Results Overall, 12.5% of our participants have regular habits of coarse food grain intake (at least 4 days/week). Age was positively associated with both systolic blood pressure (SBP) and diastolic blood pressure (DBP) (all Ps for trend < 0.05). With multivariable adjustment, including for body mass index and physical activity level, the frequency of coarse food grain intake was inversely associated with both SBP and DBP (all Ps for trend < 0.05). Similar associations were observed for estimated daily coarse food grain intake with SBP (β coefficient ± SE = −0.039 ± 0.017, P = 0.024) and DBP (β coefficient ± SE = −0.033 ± 0.013, P = 0.016). Conclusions In our sample of young Chinese adults, higher coarse food grain intake was associated with lower SBP and DBP.